Characteristics of the Ti1.27Fe + 11 wt.% Ni Composite Obtained by Arc Melting and Ball Milling - J. Bonifacio-Martínez; F. Ureña-Núñez; J. L. Iturbe-García (Journal of Chemistry)
The Ti1.27Fe + 11 wt.% Ni composite synthesized by arc melting and ball milling and its possible use in hydrogen storage were studied. First the intermetallic Ti1.27Fe was obtained from elemental powders of Ti and Fe by using the arc melting in argon atmosphere and was cracked in a reactor, after that nickel powder was added to the Ti1.27Fe alloy before the milling. The mixture was subjected to high-energy ball milling to produce the Ti1.27Fe/Ni composite. Nanocrystalline phases Ti1.27Fe + Ni were observed after 5 h of milling. Hydrogenation results indicated that in the first cycle of hydriding the maximum amount of hydrogen release was 2.10 wt.% for the composite at 100∘C, under hydrogen pressure of 0.8 MPa and without prior activation.